Financování investiční činnosti obce - Borč, Ondřej (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Bakalářská práce popisuje financování investičních činností v obcích. Zabývá se veřejnou správu ČR, možnými zdroji financování včetně dotačních programů České republiky a Evropské unie. Rozebírá finanční situaci konkrétní obce. Cílem práce je zhodnocení investičního projektu v obci, jeho financování a analýza dalšího možného způsobu.

The bachelor thesis describes the financing of investment activities in municipalities. It deals with the public administration of the Czech Republic, possible resources of financing, including grant programs of the Czech Republic and the European Union. It analyzes the financial situation of a particular municipality. The aim of the thesis is to evaluate the investment project in the municipality, its financing and analysis of another possible way.
Financing of the municipality's investment activities
Keywords: Veřejná správa; financování; vlastní zdroje; cizí zdroje; fondy Evropské unie; dotace; investiční projekt; městys; public administration; financing; own resouces; foreign resources; the funds of the European Union; grants; investment project; municipality